Truncated O‐glycans promote epithelial‐to‐mesenchymal transition and stemness properties of pancreatic cancer cells. Issue 10 (7th August 2019) - Thomas, Divya; Sagar, Satish; Caffrey, Thomas; Grandgenett, Paul M.; Radhakrishnan, Prakash
Abstract: Aberrant expression of Sialyl‐Tn (STn) antigen correlates with poor prognosis and reduced patient survival. We demonstrated that expression of Tn and STn in pancreatic ductal adenocarcinoma (PDAC) is due to hypermethylation ofCo re 1s ynthase specificm olecularc haperone (COSMC) and enhanced the malignant properties of PDAC cells with an unknown mechanism. To explore the mechanism, we have genetically deleted COSMC in PDAC cells to express truncated O‐glycans (SimpleCells, SC) which enhanced cell migration and invasion. Since epithelial‐to‐mesenchymal transition (EMT) play a vital role in metastasis, we have analysed the induction of EMT in SC cells. Expressions of the mesenchymal markers were significantly high in SC cells as compared to WT cells. Equally, we found reduced expressions of the epithelial markers in SC cells. Re‐expression of COSMC in SC cells reversed the induction of EMT. In addition to this, we also observed an increased cancer stem cell population in SC cells. Furthermore, orthotopic implantation of T3M4 SC cells into athymic nude mice resulted in significantly larger tumours and reduced animal survival. Altogether, these results suggest that aberrant expression of truncated O‐glycans in PDAC cells enhances the tumour aggressiveness through the induction of EMT and stemness properties.